Seismic design for nuclear installations : specific safety guide. (Safety standards series ;, 2021)
"This Safety Guide provides recommendations on how to meet the applicable safety requirements in relation to the design aspects of new nuclear installations subjected to seismic hazard. These recommendations focus on the consistent application of methods and procedures, in accordance with best practice, for seismic analysis, design, testing and qualification of structures, systems and components. New recommendations include applications of seismic isolation systems, the seismic margin to be achieved by the design and application of the graded approach. This Safety Guide is intended for use by organizations involved in the seismic design of nuclear installations, in analysis, verification and review, and in the provision of technical support, as well as by regulatory bodies."--